(untitled) (Czech Journal of International Relations, 2024)
Pavel Winkler: born 1910, graduated from the Law Faculty of the Comenius University in Bratislava. From July 1945 to 1970, he worked in the diplomatic service of the Ministry of Foreign Affairs, mostly in the international law department, of which he was the head in the years 1953-1966. In 1953-1954, he served as Deputy Head of Delegation at the Neutral Repatriation Commission in Korea. In 1956-1958, he participated in the establishment of the International Atomic Energy Agency and became the first chairman of the Board of Governors of this organization. In the years 1966-1970 he was ambassador to Switzerland. In 1970 he was retired for political reasons. Since 1990, he has been a consultant to the international law department of the Ministry of Foreign Affairs.